Accuracy of perceived physical activity and fitness levels among childhood cancer survivors. Issue 9 (16th June 2021) - Ha, Lauren; Mizrahi, David; Cohn, Richard J.; Simar, David; Wakefield, Claire E.; Signorelli, Christina
Abstract: Background: Childhood cancer survivors do not engage in sufficient physical activity and have low fitness levels. Perceived physical activity and fitness levels may influence survivors' engagement in health behaviours. We aimed to investigate survivors' perceptions of physical activity and fitness levels and identify how accurate their perceptions were. We further explored survivors' attitudes toward physical activity, including perceived importance and desire to increase activity levels. Procedure: We recruited 116 childhood cancer survivors (8–18 years) and assessed their perceived physical activity levels using a questionnaire and the Godin's Leisure Score Index. Accuracy of their perceptions was established by comparing their perceived physical activity levels with the recommended guidelines. Survivors reported their perceived fitness levels using the International Fitness Scale. We compared survivors' perceptions with their performance on the 6‐minute walk test using weighted Cohen's kappa to determine interrater agreement between perceived and objectively measured fitness. Results: Most survivors did not meet the physical activity guidelines (<420 min/week). One‐third incorrectly perceived whether their self‐reported physical activity levels were appropriate (84% underestimated, while 16% overestimated). Survivors had average fitness and were inaccurate at perceiving their fitness level. Survivors highly valued the importance of being able to do physical activity, and 89% reported a desire to increase their physical activity. Conclusions: Our results reveal that many survivors are not accurate when perceiving their physical activity and fitness levels. Emphasising the need for objective fitness assessments, and patient education in clinical practice may support survivors to accurately perceive their physical activity and fitness levels, thus improving health behaviours.